Sphingosine-1-phosphate stimulates colorectal cancer tumor microenvironment angiogenesis and induces macrophage polarization via macrophage migration inhibitory factor - Wu, Fang; Feng, Zhaode; Wang, Xuan; Guo, Yingcong; Wu, Bingcong; Bai, Shuheng; Lan, Ning; Chen, Min; Ren, Juan (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) is the most common gastrointestinal malignancy with extensive reprogramming of sphingolipid metabolism. However, the role and mechanisms of sphingosine-1-phosphate (S1P), a key bioactive molecule in sphingolipid metabolism, remain insufficiently characterized. Therefore, this study integrated multi-omics data to elucidate the characteristics and functions of S1P within the tumor microenvironment (TME) and investigated its role in angiogenesis through in vitro experiments.MethodsWe used bulk RNA sequencing data sets (RNA-seq) to study the prognostic value and clinicopathological characteristics of the increased synthesis of S1P. In order to elucidate the contribution of S1P to the complexity of the tumor microenvironment, we employed intercellular communication analysis and functional enrichment analysis at the single-cell transcriptome (scRNA-seq) level. The expression of Sphingosine kinase 1 (SPHK1) in human tissues was verified by immunohistochemical staining (IHC). Then, we inhibited the synthesis of S1P by suppressing SPHK1 at the cellular level to explore the changes in the pro-angiogenic function of tumor cells and M2-like macrophages, as well as the direction of macrophage polarization.ResultsS1P activity is elevated in the TME of CRC, and the increased synthesis of S1P suggests poor prognosis and early metastasis. intercellular communication analysis indicates that high S1P epithelial cells can promote angiogenesis and influence the polarization of tumor-associated macrophages (TAMs) through the macrophage migration inhibitory factor (MIF) pathway. TAMs were grouped according to gene expression patterns, in which, PCLAF+ cluster TAMs showed significantly high S1P activity, contributing to tumor growth and angiogenesis. IHC demonstrated elevated levels of SPHK1 protein expression in CRC tumor tissues. Inhibition of the synthesis of S1P in tumor cells and macrophages suppressed macrophage M2 polarization levels and reversed the pro-angiogenic phenotype by inhibiting VEGFA protein expression. Spatial transcriptomics revealed a correlation between the distribution of SPHK1 and M2-like macrophage.ConclusionsBy integrating multi-omics data and further cellular experiments, we propose that inhibition of S1P may play an important role in inhibiting angiogenesis and reversing M2-type macrophage polarization, demonstrating its anti-tumor efficacy in CRC.